2013
DOI: 10.1021/ja4040895
|View full text |Cite
|
Sign up to set email alerts
|

Highly Stereoselective Olefin Cyclopropanation of Diazooxindoles Catalyzed by a C2-Symmetric Spiroketal Bisphosphine/Au(I) Complex

Abstract: A spiroketal bisphosphine (SKP) derived chiral digold complex is identified as a powerful catalyst for the highly diastereo- and enantioselective synthesis of spirocyclopropyloxindoles from diazooxindoles and a broad range of alkenes, including both cis and trans 1,2-disubstituted alkenes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
81
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 332 publications
(81 citation statements)
references
References 77 publications
0
81
0
Order By: Relevance
“…The asymmetric catalytic cyclopropanations of electron-deficient oxindolic olefins were generally realized with Michael-Initiated Ring-Closing sequence (MIRC) reaction 9. Moreover, olefin cyclopropanation with diazooxindoles via the carbene transfer could also give access to these targets 10. Based on our long-term endeavor in the development of chiral catalysts stemmed from metal/ N , N ′-dioxide complexes11 as well as our previous study of oxindole derivatives,12 we envision that a chiral Lewis acid catalyst of N , N ′-dioxide could bind 3-alkenyl-oxindoles into a perfect chiral environment, benefiting the cyclopropanation of a free carbene generated from spontaneous decomposition of phenyliodonium ylide malonate (Scheme 1b).…”
Section: Introductionmentioning
confidence: 99%
“…The asymmetric catalytic cyclopropanations of electron-deficient oxindolic olefins were generally realized with Michael-Initiated Ring-Closing sequence (MIRC) reaction 9. Moreover, olefin cyclopropanation with diazooxindoles via the carbene transfer could also give access to these targets 10. Based on our long-term endeavor in the development of chiral catalysts stemmed from metal/ N , N ′-dioxide complexes11 as well as our previous study of oxindole derivatives,12 we envision that a chiral Lewis acid catalyst of N , N ′-dioxide could bind 3-alkenyl-oxindoles into a perfect chiral environment, benefiting the cyclopropanation of a free carbene generated from spontaneous decomposition of phenyliodonium ylide malonate (Scheme 1b).…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] Therefore, spirocyclic oxindole scaffolds have continued to draw attention in recent years. [8][9][10][11][12] Since the pioneering work of Nozaki and Noyori, 13 the transition metal-catalyzed asymmetric cyclopropanation between diazo compounds and alkenes has emerged as a powerful strategy for the synthesis of cyclopropane derivatives. [5][6][7] As a result, great efforts have been directed toward asymmetric construction of these scaffolds.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the authors demonstrated that the chiral bisgold complex Au6 , derived from the spiroketal bisphosphine ligand, was a very efficient promoter of the cyclopropanation between donor–acceptor diazooxindoles such as 9 and a broad range of alkenes (Scheme 6) [47]. The resulting spirocyclopropyloxindoles 10 , which are obtained in excellent yields and enantioselectivities, are appealing structures from a medicinal point of view.…”
Section: Reviewmentioning
confidence: 99%